A comprehensive study on thermal conductivity of the lithium‐ion battery. (3rd February 2020) - Wei, Lichuan; Lu, Zhao; Cao, Feng; Zhang, Liyu; Yang, Xi; Yu, Xiaoling; Jin, Liwen
Summary: The reliable thermal conductivity of lithium‐ion battery is significant for the accurate prediction of battery thermal characteristics during the charging/discharging process. Both isotropic and anisotropic thermal conductivities are commonly employed while exploring battery thermal characteristics. However, the study on the difference between the use of two thermal conductivities is relatively scarce. In this study, the isotropic and anisotropic thermal conductivities of the four commercially available lithium‐ion batteries, ie, LiCoO2, LiMn2 O4, LiFePO4, and Li (NiCoMn)O2, were reviewed and evaluated numerically through the heat conduction characteristics inside the battery. The results showed that there are significant differences in the temperature distribution in the battery caused by the isotropic and anisotropic thermal conductivities, which could affect the layout and cooling effectiveness of battery thermal management system. Furthermore, the effective thermal conductivities of porous electrodes and separator were determined to establish thermal conductivity bounds of lithium‐ion batteries combined with the thicknesses of battery components. The thermal conductivity bounds could be applied to evaluate the rationality of the thermal conductivity data used in battery thermal models. Abstract : Isotropic and anisotropic thermal conductivities of the four lithium‐ion batteries with different positive electrodes are reviewed. The maximum temperature and temperature difference of the battery employing isotropic and anisotropic thermal conductivities are approximately the same. Obvious differences are observed in temperature distributions of the battery employing isotropic and anisotropic thermal conductivities. Thermal conductivity bounds of lithium‐ion batteries are established to check the reliability of the thermal conductivity data used in battery thermal models.